REPRESENTASI FEMINISME DALAM KARYA SASTRA (Kajian Semiotika Novel “Eks Parasit Lajang” Karya Ayu Utami) - Sandra Olifia (Universitas Bunda Mulia, 2016)
Literature as one means disclosure of a person's thoughts expressed in text form either used as an expression that is packaged in a special language involving the use of symbols and signs. Inside the novel